3D Printable Drug Delivery Systems: Next-generation Healthcare Technology and Regulatory Aspects - Saxena, Anmol; Malviya, Rishabha (Current Pharmaceutical Design, 2023)
A revolutionary shift in healthcare has been sparked by the development of 3D printing, propelling us into an era replete with boundless opportunities for personalized DDS (Drug Delivery Systems). Precise control of the kinetics of drug release can be achieved through 3D printing, improving treatment efficacy and patient compliance. Additionally, 3D printing facilitates the co-administration of multiple drugs, simplifying treatment regimens. The technology offers rapid prototyping and manufacturing capabilities, reducing development timelines and costs. The seamless integration of advanced algorithms and artificial neural networks (ANN) augments the precision and efficacy of 3D printing, propelling us toward the forefront of personalized medicine. This comprehensive review delves into the regulatory frontiers governing 3D printable drug delivery systems, with an emphasis on adhering to rigorous safety protocols to ensure the well-being of patients by leveraging the latest advancements in 3D printing technologies powered by artificial intelligence. The paradigm promises superior therapeutic outcomes and optimized medication experiences and sets the stage for an immersive future within the Metaverse, wherein healthcare seamlessly converges with virtual environments to unlock unparalleled possibilities for personalized treatments.
Keywords: selective laser sintering